Engagement with smartphone-delivered behavioural activation interventions: a study of the MoodMission smartphone application. Issue 5 (28th September 2021) - Aizenstros, Abby; Bakker, David; Hofmann, Stefan G.; Curtiss, Joshua; Kazantzis, Nikolaos
Abstract: Background: Despite increased research interest in smartphone mental health applications (MHapps), few studies have examined user engagement and its determinants. MoodMission is a MHapp that targets low mood and anxiety via evidence-based techniques including behavioural activation (BA). Aims: The present study aimed to investigate (i) whether BA interventions delivered with visual psychoeducation had greater engagement than BA interventions delivered with solely written psychoeducation, (ii) whether BA interventions targeting mastery would have greater engagement than those targeting pleasure, and (iii) the relationship between level of engagement and MHapp benefit. Method: Participants downloaded MoodMission and completed activities and within-app evaluations over a 30-day period. Data from 238 MoodMission users were analysed via multi-level modelling and linear regression. Results: The average number of app-based activities completed was 5.46 and the average self-reported engagement level was in the low to moderate range. As hypothesized, higher levels of engagement significantly predicted more positive activity appraisal. Conclusions: The results suggest that BA technique beliefs are involved in MHapp engagement and future research examining user appraisals of techniques is warranted.